Institutional Management in Educational Cybernetics - Swaminatha Pillai, S. (Journal of Engineering Education Transformations, 1995)
An educational institution is an organization with a mission. lts raison d'etre is to promote its students' learning, within a curriculum acceptable to its stakeholders. These ends are to be met efficiently and cost-effectively.